Sulfur-enhanced thermoluminescence of γ-radiated zirconia - Rubio, E.; Mendoza, D.; Rodríguez, V.; Castaño, V.M. (Сверхтвердые материалы, 2015)
Sulfur-modified zirconia with various S contents have been characterized and analyzed for potential applications in dosimetry. The thermoluminescent signal induced by gamma radiation in pure zirconia and sulfated zirconia in the tetragonal phase has been considered. Experimental results show that the thermoluminescent glow peak depends on both the crystalline structure and sulfate concentration and that the response is linear for an ample range of irradiation.